2020
DOI: 10.31327/atj.v5i1.1256
|View full text |Cite
|
Sign up to set email alerts
|

Using Oil Palm Segregation Genetics to Decipher Illegitimate Seed Distribution Channels to Smallholder Farmers in Cameroon

Abstract: Planting material or seed is the most determinant factor for oil palm productivity alongside agro climatological and management considerations. A study was conducted to determine the different varieties of oil palm planted in smallholders’ plantations, the distribution channels for oil palm seeds and all the actors involved in the seed trade sector in Cameroon. This is a bid to secure the supply of only improved planting materials to smallholder farmers. 230 oil palm smallholder plantations were survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, a constraint lies in the need for the government and the scientific community to provide farmers with adequate expertise and guidance for undertaking proactive and well-informed adaptation measures [22]. The critical role of planting material or seed for oil palm productivity underscores the complexity of factors influencing agricultural outcomes, including agro-climatological and management considerations [23].…”
Section: Weaknesses Of Agriculture Policiesmentioning
confidence: 99%
“…However, a constraint lies in the need for the government and the scientific community to provide farmers with adequate expertise and guidance for undertaking proactive and well-informed adaptation measures [22]. The critical role of planting material or seed for oil palm productivity underscores the complexity of factors influencing agricultural outcomes, including agro-climatological and management considerations [23].…”
Section: Weaknesses Of Agriculture Policiesmentioning
confidence: 99%
“…The problem of using illegal seeds also occurs in palm oil-producing countries other than Indonesia. The results of the study [22] concluded that up to 65% of smallholder farms in Cameroon were found to be planted with poor planting material distributed in the different Mendelian ratios. It was further stated that the source of this poor quality planting material for these farms was deduced to come from private nursery entrepreneurs and workers of industrial plantations.…”
Section: The Role Of Seed Institutions In Accelerating Psrmentioning
confidence: 99%